Loss and Natural Variations of Blast Fungal Avirulence Genes Breakdown Rice Resistance Genes in the Sichuan Basin of China - Hu, Zi-Jin; Huang, Yan-Yan; Lin, Xiao-Yu; Feng, Hui; Zhou, Shi-Xin; Xie, Ying; Liu, Xin-Xian; Liu, Chen; Zhao, Ru-Meng; Zhao, Wen-Sheng; Feng, Chuan-Hong; Pu, Mei; et al. (Frontiers in Plant Science, 2022)
Magnaporthe oryzae is the causative agent of rice blast, a devastating disease in rice worldwide. Based on the gene-for-gene paradigm, resistance (R) proteins can recognize their cognate avirulence (AVR) effectors to activate effector-triggered immunity. AVR genes have been demonstrated to evolve rapidly, leading to breakdown of the cognate resistance genes. Therefore, understanding the variation of AVR genes is essential to the deployment of resistant cultivars harboring the cognate R genes. In this study, we analyzed the nucleotide sequence polymorphisms of eight known AVR genes, namely, AVR-Pita1, AVR-Pii, AVR-Pia, AVR-Pik, AVR-Pizt, AVR-Pi9, AVR-Pib, and AVR-Pi54 in a total of 383 isolates from 13 prefectures in the Sichuan Basin. We detected the presence of AVR-Pik, AVR-Pi54, AVR-Pizt, AVR-Pi9, and AVR-Pib in the isolates of all the prefectures, but not AVR-Pita1, AVR-Pii, and AVR-Pia in at least seven prefectures, indicating loss of the three AVRs. We also detected insertions of Pot3, Mg-SINE, and indels in AVR-Pib, solo-LTR of Inago2 in AVR-Pizt, and gene duplications in AVR-Pik. Consistently, the isolates that did not harboring AVR-Pia were virulent to IRBLa-A, the monogenic line containing Pia, and the isolates with variants of AVR-Pib and AVR-Pizt were virulent to IRBLb-B and IRBLzt-t, the monogenic lines harboring Pib and Piz-t, respectively, indicating breakdown of resistance by the loss and variations of the avirulence genes. Therefore, the use of blast resistance genes should be alarmed by the loss and nature variations of avirulence genes in the blast fungal population in the Sichuan Basin.